LITERATURE OF REVIEW THE INFLUENCE OF OPERATIONAL RISK AND CREDIT RISK ON BANKING PROFITABILITY: CASE STUDY OF PT BANK BCA TBK PERIOD 2018-2022 - Naura Salsabilla (Draf Solusi Indonesia, 2023)
This research is a literature review that examines theinfluence of operational risk and credit risk onbanking profitability. This research was conducted atBank BCA Tbk from 2018 to 2022. This research useda quantitative approach with the use of secondarydata. The statistical tool used in this research is SPSS28 for Windows. This research will test the feasibilityof the research model (Classical Assumptions) andtest the hypothesis to answer the problemformulation in the research